The Effect of Parents' Income, Lifestyle and Self-Control on Student's Saving Behavior in Sharia Economics Perspective - Ain, Hani Hilyatul; Nawawi, HM Kholil; Dewi, Reni Sinta (SMART Insight, 2024)
This study aims to simultaneously examine the effect of parental income, lifestyle and self-control on saving behavior. This analysis uses independent variables, namely the influence of parental income, lifestyle and self-control. The dependent variable is saving behavior. The sample of this research is the customers of Al-Asiyah SMK Al-Asiyah Islamic Mini Bank. Sampling was done by purposive sampling method. Data collection was carried out by distributing questionnaires directly to students as many as 90 questionnaires. Statistical method using Multiple Linear Regression Analysis, by testing the hypothesis test statistic t and f. The results of this study indicate that parents' income and self-control significantly influence students' saving behavior, while lifestyle significantly influences students' saving behavior.